Analisis Sistem Keamanan Data Pada Jaringan Tvri Sumut Untuk Meningkatkan Perlindungan Informasi - Hasibuan, Maria Hikmah; Nasution, Yusuf Ramadhan; Riyadi, Bagas Yowan (CV. ITTC INDONESIA, 2023)
In an era of rapidly developing information, it is very important to protect data, especially for institutions that handle sensitive data. With the aim of increasing data protection, this research concentrates on analyzing the data security system in the TVRI North Sumatra network. The main focus of the research was to find weaknesses in the existing security infrastructure, such as inadequate encryption procedures and weak password policies. Additionally, malware attacks and internal risks are discussed as potential security threats. There are advantages and disadvantages to evaluating current security protocols. Although some protocols, such as firewalls and intrusion detection systems, have proven successful, there is still room for improvement, especially in strengthening deeper layers of security and detecting more sophisticated attacks. This study emphasizes the importance of security awareness of TVRI North Sumatra employees and suggests training and awareness campaigns to reduce the dangers of social engineering. The results lead to policy updates, and proactive security measures. To implement these recommendations, an organized action plan and cooperation between departments is required. Regular regulatory updates, scheduled security monitoring, and investment in security technology are key to ensuring that data protection efforts continue. Overall, this research confirms that strengthening the security foundations of the TVRI North Sumatra network is critical to maintaining data confidentiality and maintaining its role as a reliable and secure information provider. This abstract provides a brief overview of the important elements of the research, provides solutions to problems encountered, and the general goal of improving data security in the TVRI North Sumatra network.